Ultrasound Examination for Cement Extrusion After Uni-Compartmental Knee Replacement - Peter Kam-To Siu; Wei-Ting Wu; Levent Özçakar; Ke-Vin Chang (Diagnostics)
A 66-year-old woman presented with persistent knee effusion three months after undergoing a cemented medial uni-compartmental knee replacement. She was afebrile and able to walk with a stick. Physical examination revealed moderate effusion. Radiographs showed posteriorly extruded cement, while computed tomography confirmed the absence of implant loosening but was unable to adequately visualize the adjacent soft tissues due to metallic artifacts. Ultrasound identified posterior cement extrusion beyond the femoral component, causing a delamination tear of the posterior capsule and indentation on the medial gastrocnemius. Knee arthrocentesis yielded 60 mL of blood-stained fluid with unremarkable analysis, and the patient reported improvement following the procedure. To our knowledge, this is the first report to highlight the unique role of ultrasound in detailing the anatomy of extruded cement and its impact on adjacent soft tissues following knee replacement. We demonstrate the critical structures that should be evaluated and how ultrasound aids in managing this postoperative complication.